2008
DOI: 10.1089/clo.2007.0063
|View full text |Cite
|
Sign up to set email alerts
|

HLA Homozygous Stem Cell Lines Derived from Human Parthenogenetic Blastocysts

Abstract: Individual HLA homozygous parthenogenetic human stem cell (hpSC-Hhom) lines have the potential for cell-based therapy in a significant number of individuals, provided the HLA haplotype is prevalent. We report the successful derivation of four stable hpSC-Hhom lines from both HLA homozygous and HLA heterozygous donors. Of these, the hpSC-Hhom-4 line carries the HLA haplotype found most commonly within the U.S. population, and is shared by different racial groups. These hpSC-Hhom lines demonstrate typical human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(108 citation statements)
references
References 20 publications
4
104
0
Order By: Relevance
“…The derivation efficiency was 5.6% (1/18) when calculated from all collected oocytes or 25% (1/4) when calculated from Day 5 blastocysts. The derivation efficiency was similar to those reported in previous reports [6,7]. These cells displayed morphologies and characteristics similar to those of normal hESCs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The derivation efficiency was 5.6% (1/18) when calculated from all collected oocytes or 25% (1/4) when calculated from Day 5 blastocysts. The derivation efficiency was similar to those reported in previous reports [6,7]. These cells displayed morphologies and characteristics similar to those of normal hESCs.…”
Section: Discussionsupporting
confidence: 88%
“…From previous reports, phESCs appear to be less stable than hESCs derived from fertilized embryos. It has been found that two of four HLA homozygous phESC lines have karyotype anomalies [7], and one of the six HLA heterozygous phESC lines is aneuploid [5]. Kim et al [27] also found that SCNT-hES-1 (the first derived phESC line), which was initially thought to be generated from somatic nuclear transfer, lost one of its two X chromosomes and duplicated chromosome 7 after long-term culturing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success in iPSCs seems to offer the advantages of hESCs without the ethical and rejection problems, although the iPSCs is not as versatile and plastic as ESCs. Revazova and collegues have established four unique HLAhomozygous human ESCs lines which have a simple genetic profile in the critical areas of the DNA that code for immune rejection, these ES cell lines will not provoke an immune reaction in large segments of the population and could serve to create a stem cell bank as a renewable source of transplantable cells for use in cell therapy to treat degenerative diseases (Revazova et al, 2008). In conclusion, although there is still a long way to go in ESCs replacement therapy to become a clinical reality for AD, PD, HD and ALS, this therapeutic approach is promising for neurodegenerative diseases.…”
Section: Prospects and Conclusionmentioning
confidence: 99%
“…However, there are serious safety concerns because iPS cells can enter tumorigenesis at a faster rate than the ES cells (2). Parthenogenetic embryonic stem (ESP) cells have been considered as a resource for cell therapy and may reduce immune rejection due to the homozygosity of the major histocompatibility complex (MHC) alleles (3,4). The ESP cells that are derived from unfertilized oocytes have a similar differentiation profiles as the ES cells in many animals, including humans (5), and may avoid the ethical and political concerns encountered when using ES cells that are derived from fertilized oocytes.…”
Section: Introductionmentioning
confidence: 99%